Early Refill of an Opioid Medication: Recognizing Personal Biases Through Clinical Vignettes and OSCEs - Wei-Hsin Lu; Perrilynn Baldelli; Phyllis Migdal; Richard Iuli; Lisa Strano-Paul; Kevin L. Zacharoff (Association of American Medical Colleges, 2022)
Introduction Efforts to improve pain education and knowledge about prescription opioid misuse and opioid/substance use disorder in undergraduate medical education continue to be inadequate. To advance educational practices and address training needs to counter the opioid epidemic, we created a longitudinal pain and addiction curriculum that includes three patient vignettes in which the patient requests an early refill of opioid medication. The goal was to introduce students to the potential impact of personal biases on health care delivery and medical decision-making with patients who have pain and/or substance use disorders. Methods Three clinical vignettes were presented to early matriculating medical students (MS 1s) using a progressive case disclosure approach in the format of a PowerPoint presentation with embedded audio interactions and follow-up audience response system questions. The same vignettes were converted into OSCEs for early clinical clerkship students (MS 3s). Results A total of 180 MS 1s participated in the case presentations, and 124 MS 3s participated in the OSCE session. There was a significant difference between students' level of comfort and individual patient requests for early prescription refills in both student cohorts. MS 1s were significantly more likely to provide the early refill to the elderly female patient compared to the two middle-age male patients, whereas a majority of MS 3s wanted more information. Discussion This module can be presented to medical students who have little clinical exposure and to health care trainees at other levels of clinical exposure.